Case report: Navigating the challenges: successful mechanical thrombectomy in a case of persistent primitive hypoglossal artery - Khan, Kamran Ahmed; Lutfi, Irfan Amjad; Shah, Jehangir Ali; Farooq, Salman; Ahmed, Shahnoor; Solangi, Bashir Ahmed; Khan, Ayan Ahmed; Zaidi, Fazal; Ammar, Ali; Qamar, Nadeem (Frontiers in Neurology, 2023)
Persistent primitive hypoglossal artery (PPHA) is a highly uncommon abnormal connection between the internal carotid artery (ICA) and vertebral artery (VA), with reported incidences ranging from 0.027 to 0.26%. Attempting endovascular intervention in such cases presents a considerable challenge as it carries a higher risk of embolization and other procedure-related complications that may affect a wide area of the brain. We present a case study involving the utilization of mechanical thrombectomy (MT) to treat an ischemic stroke in the M1 segment of the middle cerebral artery (MCA) despite the presence of PPHA. Performing mechanical thrombectomy in an anomalous vascular connection is feasible; however, it necessitates heightened vigilance, thorough knowledge of the anatomy, and utmost caution.